Do patients have duties? (Journal of medical ethics, 2007)
The notion of patients’ duties has received periodic scholarly attention but remains overwhelmed by attention to the duties of healthcare professionals. In a previous paper the author argued that patients in publicly funded healthcare systems have a duty to participate in clinical research, arising from their debt to previous patients. Here the author proposes a greatly extended range of patients’ duties grounding their moral force distinctively in the interests of contemporary and future patients, since medical treatment offered to one patient is always liable to be an opportunity cost (however justifiable) in terms of medical treatment needed by other patients. This generates both negative and positive duties. Ten duties—enjoining obligations ranging from participation in healthcare schemes to promoting one’s own earliest recovery from illness—are proposed. The characteristics of these duties, including their basis, moral force, extent and enforceability, are considered. They are tested against a range of objections—principled, societal, epistemological and practical—and found to survive. Finally, the paper suggests that these duties could be thought to reinforce a regrettably adversarial characteristic, shared with rights-based approaches, and that a preferable alternative might be sought through the (here unexplored) notion of a “virtuous patient” contributing to a problem-solving partnership with the clinician. However, in defining and giving content to that partnership, there is a clear role for most, if not all, of the proposed duties; their value thus extends beyond the adversarial context in which they might first be thought to arise.